PEMBUATAN ARANG 4 JENIS BAMBU DENGAN CARA TIMBUN - Tjutju Nurhayati (Jurnal Penelitian Hasil Hutan, 1990)
A study on  charcoal  manufacture  using  pit   method was  carried out 4 bamboo   species from West Java, namely andong (Gigantochloa verticillata Munro), ater   (Gigantochloa ater  Kurz), bitung (Dendrocalamus asper Back) and tali (Giganiochloa apus  Kurz). The  charcoal produced  which  was  completed   after 2 days,  were  then  subjected   to chemical analysis. The analysis consist of specific gravity, moisture content, ash, volatile  matter  and  fixed   carbon.  In addition to the aboue test, the charcoal of each species were tested  in blacksmith   which  manufacture  chopping knife.The  result  shows that out of the 4 bamboo  species tested,  ater seems to  be the  best  with  regard to  charcoal yield, chemical  properties  and application in blacksmith  work.